An examination of Hellison's (2003) Teaching Personal and Social Responsibility model, its validity and effectiveness for primary school aged children in New Zealand : a thesis in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Albany, New Zealand - Smith, Michael Hayes (Massey University, 2014)
The Hellison (2003) model was developed with a goal to enable any participant in its application to develop their personal and social responsibility. The literature demonstrates that the model has been typically made available for youth, as an after-school programme option, in which participation is voluntary. This thesis examined a longitudinal intervention over one scholastic year of an application of Hellison’s (2003) model as part of the curriculum in a New Zealand primary school. Within the model, the five levels of personal and social responsibility, 1) Respect, 2) Participation, 3) Self-direction, 4) Caring, and 5) Outside the training venue, are already translated into five operationalised goals; 1) Self-control and respect, 2) Self-motivation, 3) On-task independence, 4) Sensitivity and responsiveness, and 5) Trying these ideas in other areas of life. The intervention, a forty week training programme using a ten lesson plan format, repeated four times, utilised the goal structure of the model to formulate the individual lesson plans. The lesson plans, to convey the five social goals of the model in accordance with Hellison’s (2003) guidelines, included a karate skill set as the physical activity component of the training sessions. Two cohorts were recruited into the study, from two scholastically equivalent schools, one to receive the intervention (n = 36), and one to act as control (n = 49). The control group completed the measures only and did not receive the intervention. Each goal of the model was empirically assessed to determine change over time whilst participating in the current application of the model. A time series empirical approach was used and psychometrically reliable and valid instruments were administered at six equal-distant intervals. At each of the six intervals, four self-reporting measures were completed by the child participants. Rosenberg’s Self-Efficacy Scale (S-ES), Dishman’s Self-Motivation Inventory for Children (SMI-C9), Muris’s Self-Efficacy Questionnaire for Children (SEQ-C), and Caprara and Pastorelli’s Prosocial Behavior Scale. A separate measure, Polit’s Positive Behavior Scale, was completed each by the participant’s parent, and the participant’s class teacher, at each of the six intervals. Statistical analysis using regression model fitting on the data obtained from the empirical measures demonstrated that scores increased for the intervention participants on each measure over the course of the current study. A linear model was evident from the analysis. Multivariate repeated analysis of the four child self-reporting measures demonstrated that the mean positive change, on goals 1 - 4, was greatest for the intervention group. Equality of means analysis also confirmed that the intervention group had the highest level of improvement in positive behaviour, as reported by the parents and teachers, on goal 5. Secondary analysis using Guttman (1947, 1950) scaling enabled a detailed examination of the model’s stage-like progression premise. The intention of the analysis was to determine if any participant could progress through the five stages, each in succession, as the model posits that they should. Scalograms were constructed at each of the six intervals to produce a Coefficient of Reproducibility, one each for the intervention and control groups. From the twelve coefficients, a mean Coefficient of Reproducibility ≥ .90 was acceptable evidence of temporal reliability of the scalograms in the current study. Guttman (1950) Scalogram Analysis demonstrated that a four-item scalogram, for the child self-reporting measures, and a five-item quasi-scalogram, combining the child self-reporting measures with a mean score of the parent and teacher measure, was found in the current study. In a research first, the Teaching Personal and Social Responsibility model was demonstrated to possess stage progression in its goal structure. Further, participants in the intervention group demonstrated that they progressed along a single continuum, one stage after another, as the Hellison (2003) model claimed. However, the goals in the current study developed in a differing order than those proposed by the Hellison (2003) model. Specifically, the stage sequence discovered was firstly goal 2) Self-motivation, followed by goal 3) On-task independence, before goal 1) Self-control and respect, which was third. Goal 4) Sensitivity and responsiveness, and 5) Trying these ideas in other areas of life, emerged in the sequence as the model predicted. A repeated, between groups, analysis demonstrated that a significant difference between the intervention group and control group existed from sixteen weeks and beyond. The findings from the current study make a significant contribution to the literature. A detailed, empirical protocol, a research first of its type, was demonstrated to be reliable for the assessment of participant development whilst engaged in an application of the model. A revised Hellison (2003) model was valid, and effective, for the intervention participants as the model posits. A wider application of the Hellison model is warranted and continued research is recommended. A replication of the current study, as well as research of a school-wide application, of the revised Hellison (2003) model is suggested.
Keywords: Donald R. Hellison; Hellison's model; Personal and social responsibility; Social responsibility; Teaching social responsibility; Primary school children; Physical education; Motivation